A detailed comparison of antenna impedance measurements on ASDEX Upgrade with the ion cyclotron range of frequencies antenna code TOPICA. (4th September 2015) - Stepanov, I.; Noterdaeme, J.-M.; Bobkov, V.; Faugel, H.; Coster, D.; Milanesio, D.; Maggiora, R.; Siegl, G.; Bilato, R.; Brambilla, M.; Verdoolaege, G.; Braun, F.; et al.
Abstract: New antenna diagnostics on the ASDEX Upgrade, in the form of voltage and current probe pairs on the feeding lines of each ion cyclotron range of frequencies antenna, close to the input ports, have made it possible to study in detail the behavior of the ASDEX Upgrade two-strap antenna under changing loading conditions, and compare these measurements with the results of simulations using the TOPICA code. The present work extends previous studies by using the input impedance (more precisely, the complex voltage reflection coefficient ) on each antenna port for comparison, instead of the more commonly used loading resistance or coupled power. The electron density profiles used for the simulation were reconstructed from the deuterium-carbon-nitrogen interferometer and lithium beam emission spectroscopy measurements, edge-localized mode-synchronized and averaged over time intervals from 10 to 200 ms depending on the case; 112 cases were compared from seven ASDEX Upgrade discharges with widely different plasma parameters and two operating frequencies (30 and 36.5 MHz). Very good agreement in was found with the measurements on antenna 3 (<3% averaged over a shot), and good agreement was found with antennas 1 and 2 (<10%); the code reproduced the correct trend in loading resistance in a significant majority of cases, although the discrepancies in the absolute values were rather high (up to  ∼50%) due to high reflection. Sources of discrepancy are discussed.